2019
DOI: 10.1002/slct.201902506
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Conformation and Crystal Packing in Aryl Propargyl Ethers: Structural and Spectroscopic Properties of 2‐(prop‐2‐yn‐1‐yloxy)acene Derivatives

Abstract: The 2-(prop-2-yn-1-yloxy)naphthalene (compound I) and 1nitro-2-(prop-2-yn-1-yloxy)benzene (compound II) were prepared in excellent yields by the reaction of propargyl bromide with 2-naphthol and 2-nitrophenol, respectively. Structural and conformational properties of both compounds have been analyzed using a combined approach including single-crystal X-ray diffraction and quantum chemical calculations. Two forms are found to be stable and nearly isoenergetic conformers, depending on the mutual orientation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Thompson and Day also reported that flexible molecules often do not adopt their lowest energy form (global minimum) in crystal structures but rather the form that optimizes the balance of inter- and intramolecular interactions . In addition, the interplay between different conformers and the crystal structure of aryl propargyl ether derivatives was also attributed to intermolecular interactions …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thompson and Day also reported that flexible molecules often do not adopt their lowest energy form (global minimum) in crystal structures but rather the form that optimizes the balance of inter- and intramolecular interactions . In addition, the interplay between different conformers and the crystal structure of aryl propargyl ether derivatives was also attributed to intermolecular interactions …”
Section: Results and Discussionmentioning
confidence: 99%
“…55 In addition, the interplay between different conformers and the crystal structure of aryl propargyl ether derivatives was also attributed to intermolecular interactions. 56 Insights into Supramolecular Packing. All compounds were analyzed at the supramolecular level focusing on polymorphs 1a and 2a,d to understand the packing of the obtained crystals.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%